Using Mobile Phone to Overcome Students’ Anxiety in Speaking English - Machmud Karmila; Abdulah Ridwan (SHS Web of Conferences, 2018)
The goal of this research is to discover whether the use of mobile phone can minimize students’ anxiety in speaking English and in turn will improve their speaking skill. Anxiety has become a major problem for students when asked to speak in a speaking class. Using quasi experimental method, the data of this research was collected through questionnaire of foreign language anxiety classroom scale, and oral test for speaking ability. Factorial design 2 x2 using ANOVA is used to analyze the data of this research. The result has shown: (1) the score of students’ learning achievement in speaking English who were taught by using mobile phone application was higher than the students’ who were taught by using conventional teaching. It means that the use of mobile phone application results in better influence towards students’ speaking ability; (2) The learning achievement of the students with high anxiety in speaking English who were taught by using mobile phone application was higher than the high-anxiety students who were taught by conventional teaching; (3) The learning achievement in speaking English of low anxiety students who were taught by using mobile phone application was higher than low anxiety students’ who were taught by conventional teaching.